PWM Based VSC For Power Quality Assessment of Grid Integrated DFIG-WECS - Soomro, M.A; Memon, Z.A; Kumar, M. (International Journal of Integrated Engineering, 2020)
The socioeconomic indicators are exclusively dependent upon the growth of energy for every country. The rise of population and urbanization on one hand and environmental degradation by fossil fuel sources on the other has realized the world for sustainable sources of energy to meet the energy imbalance. Therefore, high penetration of wind energy is need of the hour to meet the challenge of rising consumption of power. Globally, wind energy trends are witnessing a rapid growth with the passage of time. In this research contribution, the Doubly Fed Induction Generator (DFIG) derived wind power generation has been selected to harness wind energy at variable speed. The uncertain and fluctuating nature of wind flow cause power quality problems. MATLAB simulation model has been designed and response of power quality issues like voltage sag and harmonic distortion is checked both at No load and with load at the point of common coupling (PCC). For smooth integration of wind turbine generator with power grid, pulse width modulated (PWM) voltage source converters (VSC) are used both at the rotor side converter (RSC) and the grid side converter (GSC). Proportional integral (PI) controllers are used along with VSC for high power output.